Promising Practices for Building Cybersecurity Knowledge, Confidence and Capacity among College Professors (Journal of The Colloquium for Information Systems Security Education, 2017)
There has been increasing awareness that any scalable and sustainable effort to grow the workforce in cyber security cannot focus only on university students, but also college professors. Many are looking to higher education to produce skilled and capable cybersecurity professionals but little is known about what these professors really need. Utilizing data gleaned from focus groups and surveys with college and university computer science professors (N=30) that participated in a cybersecurity professional development program at a leading urban university, this research aims to identify promising practices for building cybersecurity knowledge, confidence and capacity among college professors. Results indicated that the participating computer science professors had experience with cybersecurity but were not confident in their teaching skills in this area. Participants reported that the hands on and applied activities in the professional development training supported both knowledge and confidence building. They attributed their capacity to build coursework at their respective institutions to the materials provided during the professional development. However, findings also suggest that without ongoing mentorship, collaboration and diversity training, capacity building might be limited. These results contribute to a greater understanding of evidence based practices with college professors in cybersecurity.
Keywords: Cybersecurity; Qualitative; College Professors; Education